Commonality of Virulence-Promoting Function in Rhodococcus equi Virulence Associated Proteins (Vaps) - Timothy R. Ganderton; Daniel Ghete; Karen Hogg; Graeme J. Park; Christoph G. Baumann; Anthony J. Wilkinson; Paul R. Pryor (Cellular Microbiology)
Rhodococcus equi is a Gram-positive facultative intracellular pathogen associated with life-threatening bronchopneumonial disease in foals. Key to R. equi’s intracellular survival in host macrophages is the production of virulence associated proteins (Vaps). Numerous vap genes are found on virulence plasmids isolated from different species, and the Vaps share a high degree of sequence identity. VapA has been extensively studied, and although vapK and vapN genes from other R. equi virulence plasmids have been shown to be essential for R. equi intracellular survival, their mode of action is less characterised. We, therefore, examined whether VapK and VapN worked mechanistically in the same way as VapA. Indeed, like VapA, VapK and VapN neutralised lysosomal pH and reduced lysosomal hydrolase activity. A loss of VapA and R. equi virulence could be regained by the presence of either VapK or VapN. The acid-neutralisation activity was also observed to a lesser extent with VapB. There was a differential activity across these virulence-promoting Vaps with the most “acid-neutralising” activity found with VapN, then VapA and K, and finally VapB. These data suggest that VapA production, which is often found in equine infections, can be substituted by VapK and B (produced by plasmids often found in porcine species) or VapN (produced by plasmids often isolated in bovine and human samples). These data imply that the molecular mechanism(s) that VapA uses to neutralise lysosomal acidity should also be seen in VapN and K which will help guide researchers in identifying their precise mode of action and aid the future development of targeted therapeutics.